The effect of Herbal medicine Silybum marianum (L.) Gaertn. seed extract on galactose induced cataract formation in rat - H Fallah Huseini; AB Zaree; A Babaei Zarch; R Heshmat (Institue of Medicinal Plants, ACECR, 2004)
In diabetic condition the oxygen free radical and reduced glutathione level are the important risk factor for cataract formation. The preventive effect of antioxidant and increased cellular glutathione level on cataract formation reported in experimental studies. However in present study silybum marianum seed extract (silymarin) due to its antioxidative property, increased cellular glutathione level and cellular membrane stabilizing properties was tested against development of galactose-induced cataract. Thirty male rats of 45 days old were divided in three groups and placed in same environmental condition. One group kept as healthy control, feed on normal rat chew, second group received 30% galactose diet, and third group received 30% galactose diet as well as silymarin orally in the dose of 200 mg/kg daily. Cataract development was observed by ophthalmoscope and necked eye in both the groups of animal during the 40 days of the study. The glutathione and lipid peroxides were determined after 20 days in one lens of all rats. Results indicate that in control group first stage of cataract development were observed after 7 to 9 days and fourth stage after 29 to 35 days. In silymarin treated group all stages of cataract development were significantly delayed as compared to control group. The first stage of cataract development were observed after 19 to 23 days and fourth stage after 37 to 43 days in only 60% of animals. These results indicate that silymarin retarded the process of cataract development in galactose-fed rats. In conclusion the preventive effect of silymarin on galactose induced cataract formation may be due to antioxidant, anti-inflammatory, increased cellular glutathione level and membrane stabilizing properties of this herbal medicine.